Pricing-to-market or hysteresis? An empirical investigation of German exports - Emilia Penkova (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2005)
The paper initiates a new area of research: both concepts of hysteresis and pricing-to-market are simultaneously investigated in relation to German exports into Belgium, France, Italy, UK, Spain and Sweden over the period 1975 to 1994 at 4-digit ISIC level. There is abundant empirical evidence that German exports price-to-market. Part of this observed limited exchange rate pass-through, however, might be due to hysteresis as well. A dynamic panel estimation is undertaken, a new concept 'pricing-to-market due to hysteresis in quantities' is introduced, and a method for capturing it is proposed. A test for measuring hysteresis in prices is also suggested. There is evidence that hysteresis and pricing-to-market deserve a better empirical modelling.
Keywords: C23; F14; 330; international trade; panel data